Prenatal identification of an inverted duplicated 13q marker chromosome with a neocentromere - Liselot van der Laan; Daniel R. Hoekman; Esther J. Wortelboer; Marcel M. A. M. Mannens; Angelique J. A. Kooper (Molecular Cytogenetics, 2023)
Abstract In this case report, we describe a rare prenatal finding of a small marker chromosome. This marker chromosome corresponds to an inverted duplication of the 13q region 13q31.1q34 (or 13q31.1 → qter) with a neocentromere, detected during genetic analysis of a chorionic villus sample in a fetus with multiple congenital anomalies after a normal prenatal screening result by noninvasive prenatal testing.